The state of rheological properties of blood in pregnant smokers with chronic nonspecific bronchial inflammation - Anna V. Dzyubailo; Viacheslav S. Lotkov (ZAO "Consilium Medicum", 2024)
Aim. To evaluate the effect of smoking on the blood rheology of pregnant smokers with chronic nonspecific bronchial inflammation. Materials and methods. The prospective study included 107 pregnant smoking patients and 136 non-smoking pregnant women who were observed in a polyclinic. The control group consisted of 42 non-smoking women without chronic diseases. The patients were examined according to the clinical guidelines for the treatment of chronic obstructive pulmonary disease. The speed and volume indicators of the function of external respiration, indicators of blood rheology were studied. The reliability of the results was assessed using the methods of parametric and nonparametric statistics. Before applying all statistical research methods, it was checked whether the sample obeys the Gaussian (normal) distribution law. A single-factor analysis of variance was used to determine whether there was a statistically significant difference between the averages of three or more independent groups. Results. Having refuted the null hypothesis about the absence of the effect of smoking on hemoglobin, using the Student's t-test method for dependent samples, it was established. Conclusion. The longer the period of tobacco use lasted, the more likely it was to develop changes in the viscosity qualities of blood, which undoubtedly affected the condition of patients and the fetus.